Intrinsic risk factors of non-contact quadriceps and hamstring strains in soccer: a prospective study of 100 professional players. Issue 9 (30th November 2010) - Fousekis, Konstantinos; Tsepis, Elias; Poulmedis, Peter; Athanasopoulos, Spyros; Vagenas, George
Abstract : Objectives: To identify the intrinsic risk factors of non-contact strains in the hamstrings and quadriceps muscles of professional soccer players via a cohort prospective design. Methods: A total of 100 professional soccer players (aged 19.4–27.8 years) from four professional teams underwent a composite musculoskeletal assessment at preseason. Intrinsic risk factors included dichotomies of asymmetries in muscle strength, flexibility, proprioception, anthropometry and knee joint stability, and of previous injuries. Muscle strains were prospectively monitored during the subsequent season using questionnaires. The data were analysed via binary logistic regression. Results: Thirty-eight percent of the players sustained one or more lower-extremity muscle strains. Sixteen (42.1 %) and seven (18.4 %) of them were clinically diagnosed as having non-contact muscle strains at their hamstrings and quadriceps, respectively. Players with eccentric hamstring strength asymmetries (OR=3.88; 95% CI 1.13 to 13.23), functional leg length asymmetries (OR=3.80; 95% CI 1.08 to 13.33) and no previous hamstrings injuries (OR=0.15; 95% CI 0.029 to 0.79) were at greater risk of sustaining a hamstring muscle strain. Players with eccentric strength (OR=5.01; 95% CI 0.92 to 27.14) and flexibility asymmetries (OR=4.98; 95% CI 0.78 to 31.80) in their quadriceps as well as heavier (OR=10.70; 95% CI 0.73 to 156.37) and shorter players (OR=0.08; 95% CI 0.00 to 1.35) were at greater risk of sustaining a strain in this muscle group. Conclusions: Professional soccer players with functional asymmetries possess a higher risk of sustaining hamstring strains. Previous injury seems not to constitute a risk factor. The systematic isokinetic evaluation of the lower extremities during the preseason period can provide therapists and trainers with valuable data regarding the predictive elements of non-contact hamstring strains in professional soccer players.